213k views
5 votes
Help me please. i need help its for math

Help me please. i need help its for math-example-1

1 Answer

2 votes

When
x=-6, the value of the expression becomes undefined so it is the non-permissible replacement for the expression.

Explanation:

Step 1:

To determine the non-permissible replacement we substitute x with the values of 6, 3, -3, and -6.

When
x=6, (3-x)/(6+x) = (3-6)/(6+6)=-(3)/(12) = -(1)/(4),

When
x=3, (3-x)/(6+x) = (3-3)/(6+3)=(0)/(9)=0,

When
x=-3, (3-x)/(6+x) = (3-(-3))/(6+(-3))=(6)/(3) =2,,

When
x=-6, (3-x)/(6+x) = (3-(-6))/(6+(-6))=(9)/(0), any value, when divided by a zero, becomes undefined.

Step 2:

The values of options a, b, and c all have numerical values.

When
x=-6, the value of the expression becomes undefined so it is the non-permissible replacement for the expression.

User Luc Franken
by
5.1k points